Urgensi Sosialisasi Pola Asuh Bagi perkembangan Anak di Desa Maukeli - Yohanes Bergamans Berek Manehat; Veronika I. A Boro; Masiximus Ardon Bidi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study discusses the influence of parenting patterns on children's social development in Maukeli Village, Mauponggo District, Nagekeo Regency. Community service activities in the form of socialization carried out on May 14, 2025 aimed to increase the understanding of mothers and the community regarding the importance of healthy and positive parenting patterns in supporting the growth and formation of children's character. The methods used include lectures, discussions, simulations, evaluations, and feedback, involving mothers and children as participants. The results of the activity show that the parenting patterns applied in Maukeli Village are still diverse, so this socialization provides knowledge and practical skills in child care that can shape children's character and emotional development optimally. This activity emphasizes the importance of the active role of mothers as primary caregivers and collaboration between the village government, health workers, and the community in creating a conducive family environment for child development. With ongoing assistance, it is hoped that children in Maukeli Village can grow into independent, responsible, and highly competitive individuals.